The Influence of Good Corporate Governance on Profitability in Manufacturing Companies Listed in the Indonesia Stock Exchange in 2020 - Bayu Kurniawan; Mutiara Tresna Parasetya (Budapest International Research and Critics University, 2021)
This research on profitability aims to examine the effect of good corporate governance on profitability. The population in this research are manufacturing companies listed on the Indonesia Stock Exchange in 2020. The sample in this research was selected through purposive sampling, so that a sample of 163 companies was obtained. The statistical test tool uses multiple regression analysis. Profitability in this research was measured using Return on Assets, while good corporate governance was measured using the number of independent board of commissioners. The results show that the independent board of commissioners has a significant positive effect on profitability.